Suicidality among adolescents engaging in nonsuicidal self-injury (NSSI) and firesetting: the role of psychosocial characteristics and reasons for living. Issue 1 (December 2015) - Tanner, Alicia; Hasking, Penelope; Martin, Graham
Abstract Background Co-occurrence of problem behaviors, particularly across internalizing and externalizing spectra, increases the risk of suicidality (i.e., suicidal ideation and attempt) among youth. Methods We examined differences in psychosocial risk factors across levels of suicidality in a sample of 77 school-based adolescents engaging in both nonsuicidal self-injury (NSSI) and repeated firesetting. Participants completed questionnaires assessing engagement in problem behaviors, mental health difficulties, negative life events, poor coping, impulsivity, and suicidality. Results Adolescents endorsing suicidal ideation reported greater psychological distress, physical and sexual abuse, and less problem solving/goal pursuit than those with no history of suicidality; adolescents who had attempted suicide reported more severe NSSI, higher rates of victimization and exposure to suicide, relative to those with suicidal ideation but no history of attempt. Additional analyses suggested the importance of coping beliefs in protecting against suicidality. Conclusions Clinical implications and suggestions for future research relating to suicide prevention are discussed.